(untitled) (African Journal of Science, Technology and Social Sciences, 2025)
ABSTRACT The Sustainable Development Goals agenda 6.2 aims to improve access to safely managed sanitation by 2030. However, the sewer system serves only 17 % of the Sub-Saharan African population in informal settlements. Possible interventions and options to address sanitation issues in informal settlements have been advanced through research. However, upscaling and improving sanitation in informal settlements has been a challenge. The study investigated the technologies used in sanitation delivery in Mukuru Kwa Reuben. The study employed a descriptive survey design. The unit of analysis was the household level. The target population comprised the household heads involved in sanitation service provisions. Cluster and simple random sampling techniques enrolled 100 household heads from 10 clustered administrative units. Data from the questionnaires and structured observations were analysed using SPSS version 25, employing both descriptive and inferential statistics at a 5% significance level. The sanitation technologies for containment and storage of excreta/sludge included pit latrine, fresh life toilet, pour flush, cistern flush, and composting toilet. In emptying and transportation, eco bags, washing machines, transfer stations, buckets, urine containers, hand carts, trucks, and sewers were used. The excreta/sludge treatment/disposal options encompass treatment plants, septic tanks, open grounds, rivers, and landfills. There was a moderate positive correlation between accessibility and the construction/installation process of the toilet (r = .546, p < .001). There was statistically significant variation in the provision of sanitation technologies for emptying and transportation of sludge/excreta concerning accessibility (p = 0.013), availability (p = 0.047), and accountability (p < 0.001). The study concludes there was significant variation in the type of sanitation technology used and its construction/installation process, which influenced the affordability, accessibility, and availability of sanitation technologies. The study recommends upscaling of composting toilets, sewers, and treatment plants.